Tinjauan Yuridis Putusan 185/G/2022/PTUN.JKT Tentang Uji Kompetensi Mahasiswa Kesehatan Berbasis Nasional: Legal Review of Decision 185/G/2022/PTUN.JKT Concerning The National-Based Health Student Competency Test - Baharul Iman, Muhammad; Syafira, Fara (Jurnal Hukum dan Etika Kesehatan, 2025)
This research analyzes the administrative legal issues related to the issuance of the Ministerial Decree on the establishment of the National Committee for Health Student Competency Tests in Indonesia, as examined in the Jakarta Administrative Court Decision Number 185/G/2022/PTUN.JKT. This research was conducted a normative legal method, using statute  approach, conceptual approach, and case approach to assess the legal basis for the decree, the minister's authority, and its implications for the principle of academic autonomy in higher education. The findings indicate that the ministerial decree contradicts applicable laws and regulations because it transfers responsibility for implementing competency tests from higher education institutions to a centralized administrative body. The court's decision confirms that this intervention violates the principles of academic autonomy and the principle of legality in state administrative law. Furthermore, this decision highlights the importance of implementing participatory governance, ensuring legal certainty, and protecting citizens' constitutional rights in education policy. This case sets an important precedent in restructuring the relationship between state intervention and academic independence and strengthening the role of the rule of law in higher education governance.